2022
DOI: 10.1080/15592324.2022.2081420
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of DREB genes in alfalfa (Medicago sativa) in response to cold stress

Abstract: Dehydration-responsive element-binding proteins (DREBs) belong to members of the AP2/ERF transcription factor superfamily, which has been reported to involve various abiotic-stress responses and tolerance in plants. However, research on the DREB -family is still limited in alfalfa ( Medicago sativa L.), a forage legume cultivated worldwide. The recent genome-sequence release of the alfalfa cultivar “XinJiangDaYe” allowed us to identify 172 DREBs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Recently, the expression profiles of DREBs in M. truncatula and M. sativa are identified in the cold-stress response ( Shu et al, 2016 ; Sheng et al, 2022 ). A cluster of DREB subfamily members on M. truncatula chromosome 6 is induced by both cold and freezing stress ( Shu et al, 2016 ), and 33 MsDREBs are significantly upregulated by cold treatment ( Sheng et al, 2022 ). The genome-wide identification of DREBs in Medicago species provides promising molecular targets for the improvement of cold tolerance in crops.…”
Section: Cold Stressmentioning
confidence: 99%
“…Recently, the expression profiles of DREBs in M. truncatula and M. sativa are identified in the cold-stress response ( Shu et al, 2016 ; Sheng et al, 2022 ). A cluster of DREB subfamily members on M. truncatula chromosome 6 is induced by both cold and freezing stress ( Shu et al, 2016 ), and 33 MsDREBs are significantly upregulated by cold treatment ( Sheng et al, 2022 ). The genome-wide identification of DREBs in Medicago species provides promising molecular targets for the improvement of cold tolerance in crops.…”
Section: Cold Stressmentioning
confidence: 99%
“…Moreover, Fructan 1-exohydrolase w3 (Fehw3) gene contribute to the high levels of stem water-soluble carbohydrate remobilization under terminal drought stress [4]. Several authors have reported that TaDreb-B1 and Fehw3 genes are involved in abiotic stress tolerance parameters in several crops [8,[16][17][18]. Chen et al [19] reported that wheat accessions, carrying TaDreb-B1 haplotypes1 and 3, showed drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In response to external stimuli, plants’ bodies produce signals that trigger the phosphorylation of downstream proteins, which in turn trigger a number of transcription factors [ 5 ]. Ultimately, plant-associated resistance genes and associated defense systems are induced, thus altering the ability of the plant to adapt to its environment [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%